Analisis Yuridis Implementasi Pajak Penghasilan di Era Digital dalam Sistem Perpajakan Indonesia - Latifolia, Thalita Raissa; Najwa Salsabilla Asmara; Athalla Fikra Yazdaniar; Muhammad Farras Mukhlis (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This research conducts a juridical analysis of the problematic implementation of income tax on digital economic activities within Indonesia's taxation system. Digital transformation has altered the global economic landscape, yet the existing tax system has not fully accommodated the specific characteristics of the digital economy. This study aims to identify weaknesses in the income tax legal framework within the digital economy context and formulate an ideal construction for income tax regulation that can optimize tax revenue without impeding digital economic growth. The research employs a normative juridical methodology with statute approach, conceptual approach, and comparative approach. The findings indicate that current income tax provisions are ineffective in addressing digital economy challenges, particularly concerning concepts of income sources, permanent establishment, and monitoring mechanisms. The study recommends comprehensive reforms including redefinition of fundamental tax concepts, strengthening of the withholding tax system, development of tax information technology infrastructure, and harmonization with international standards. The ideal construction of income tax regulation must consider principles of legal certainty, fairness, administrative efficiency, and economic neutrality to create a taxation system adaptive to digital economic developments.